Union catalog of medical and paramedical resources in five government hospital libraries in Quezon City - Maramag, Araceli B.; Hidalgo, Namnama P.; Castillo, Regala Lucrecia (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1978)
A listing by subject and by author/title of 2,980 books, periodicals, and special materials/publications available at the libraries of five government hospitals was completed in this study. These hospitals which recently formed an administrative alliance to improve their present systems and services are the Armed Forces of the Philippines Medical Center, Government Service Insurance System General Hospital, National Orthopedic Hospital, Philippine Heart Center for Asia, and Veterans Memorial Medical Center.
This work is divided into two main sections: the subject catalog and the author and title index. The subject catalog or main sequence of the bibliography is arranged by subject based on the Medical Subject Headings of the National Library of Medicine and the Subject Headings Used in the Dictionary Catalog of the Library of Congress. Under each subject, books are arranged alphabetically by author. The periodicals and special materials are also classified and arranged alphabetically by titles. Books are listed in the first order followed by periodicals and special materials. Complete bibliographic data are given. The location symbol showing where a copy may be found and the call number of the material whenever available are provided. Each entry is preceded by an entry number.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Hospital libraries -- Philippines -- Quezon City; Medical literature -- Union lists; Medicine -- Union lists -- Philippines -- Quezon City